Group Process and Conflict in System Development - Robey, Daniel; Farrow, Dana L.; Franz, Charles R. (Management Science, 1989)
Information system development projects engage organizational members in a process with potential for conflict. Managing such conflicts in project groups is an important but often neglected aspect of systems development. This research assesses group process during the development of an information system in an insurance company, using questionnaires, recorded transcripts of group meetings, interviews, and archival data. We describe the relationships among four variables in a model of conflict—participation, influence, conflict, and conflict resolution—at five different periods over a 22-month period. Our results show that in every time period participation positively affected influence and that influence positively affected both conflict and conflict resolution. These findings are supported by an analysis of communication patterns within four project meetings and by qualitative data collected during the project. The practical implications of conflict and group processes in system development are discussed.